Analysis of Factors Affecting Seaweed Production in Malangke District in North Luwu Regency - Aswad Baharuddin (Golden Ratio of Data in Summary, 2021)
The purpose of this study was 1) to determine the partial effect of working capital factors, labor, infrastructure, and cultivated area on farmers' seaweed production. 2) To determine the simultaneous effect of factors, working capital, labor, infrastructure, and arable land area on farmers' seaweed production in Malangke District, North Luwu Regency. The population in this study were all seaweed farmers in North Luwu District, totaling 324 people. The sampling technique in this study used a simple random sampling method so that the number of samples was 76 people. The analysis model used was Multiple Regression with the help of the SPSS version 17 program. The results showed that there was a partial effect of working capital, infrastructure, and land area on farmers' seaweed production simultaneously. This is indicated by the calculated F value = 3.478 with a significance value of 0.012 less than 0.05. This indicates that if seaweed farmers want to increase seaweed productivity, they should increase the amount of working capital, labor, infrastructure, and land area together.